PEMBAGIAN HARTA BERSAMA DALAM PERKAWINAN POLIGAMI - Sofwan Ahadi (Isti`dal : Jurnal Studi Hukum Islam, 2014)
Al-Qur'an and the hadis do not regulate in detail the division of joint property in a polygamous marriage. That is why, KHI (the Compilation of Islamic Law) set the regulation on the basis of accepted practices in public life in Indonesia and not contrary to the principles of the shari'ah. In the Islamic legal system, this kind of habit called "urf? which could be the basis for determining the law. However, the provision of article 96 KHI in paragraph (1), ie, ??regarding the case of divorce of the cerai mati (divorce caused by the husband death), then half of the joint property belongs to couple living longer?. It was confusing. Therefore, when applied in a polygamous marriage, the definition of "living longer spouses" is open to multiple interpretations. Which couple should have the right to own property together? Socio-legal considerations in this article gave space to the oldest wife as the part that can be called as a "living longer". From the beginning she risked her life in marriage, which absolutely faced the challenges and trials that are not easy. Then the oldest wife should get half of the joint property before it will be given according to the inheritance law. Moreover, when viewed from the side of habit, after a new couple has just sarted to tread the prosperity that they have desired for years, suddenly the husband decided to do polygamy, it would be unfair if the legal treatment of the first wife is equated with his second wife, third or fourthKeywordsjoint property, divorce, fair, marriage Nash al-Qur'an dan hadis tidak mengatur secara rinci pembagian harta bersama dalam perkawinan poligami. Itu sebabnya, KHI mengaturnya atas dasar kebiasaan yang diterima dalam kehidupan masyarakat di Indonesia dan tidak bertentangan dengan prinsip syari'at. Dalam sistem hukum Islam, kebiasaan semacam ini disebut urf yang bisa menjadi dasar penentuan hukum. Akan tetapi, ketentuan KHI dalam pasal 96 ayat (1), yakni ??Apabila terjadi cerai mati, maka separuh harta bersama menjadi hak pasangan yang hidup lebih lama?, terasa membingungkan. Sebab, ketika diterapkan dalam perkawinan poligami, pengertian ??pasangan yang hidup lebih lama? ini bersifat multitafsir. Pasangan mana yang berhak memiliki harta bersama? Pertimbangan sosio-legal terhadap pasal ini, memberikan ruang kepada istri tertua sebagai pihak yang memenuhi kriteria sebagai ?yang hidup lebih lama?. Sejak awal ia mempertaruhkan jiwa dan hidupnya dalam perkawinan, yang tentu mendapat tantangan dan cobaan yang tidak ringan. Maka selayaknya istri tertua mendapat separuh harta bersama sebelum dibagi dalam hukum kewarisan. Apalagi, jika dilihat dari sisi kebiasaan, setelah pasangan suami-istri yang lama baru menapak kesejahteraan yang mereka idam-idamkan selama bertahun- tahun, tiba-tiba suami melakukan poligami, maka akan tidak adil kalau perlakuan hukum terhadap istri pertama disamakan dengan istri kedua, ketiga atau keempat.